Understanding the Acceptance of Local Public Officers on Computer-based Urban Spatial Information System (International Journal of Built Environment and Sustainability, 2016)
Information technology is developed to assist people in minimizing processing time, reducing errors, increasing the accuracy and simplifying the overall process. The process of recording, retrieving and displaying data and information can thus be easily and accurately undertaken. Information technology in its initial development, however, tends to be too costly and complicated to make a real particularly for people in developing countries. Fortunately, universities as the centers of innovation, can be a game changer for the adoption of the innovative processes, for the benefits of the community at large. In all Indonesian universities, this role is associated with a, so called Tri Dharma Perguruan Tinggi (Three Devotions of Higher Education, TDHE). This paper examines the acceptance of the collaborating officials and the obstacles i.e. internal and environmental factors. We proposed the use of GIS-based technology to coordinate the administrative units of local government at all levels, particularly the Kelurahan as the lowest hierarchy of the administrative unit in local government system. The Kelurahan will then be the spearhead in a local government system in Indonesia in promoting administrative services to all Citizens. We undertook an integrated training and tutorial for select official staff of the Kelurahan on the system. Evaluation of shows that the information system can be used to simplify the collaborators’ activities. The evaluation was done through in-depth interview to the collaborating officials. The collaborators interested in learning more about the system as an innovative way in providing service to the community as well as spatial data input to support urban planning and management.